An Optical Biosensor from Green Fluorescent Escherichia coli for the Evaluation of Single and Combined Heavy Metal Toxicities - Futra, Dedi (Sensors (Basel), 2015)
A fluorescence-based fiber optic toxicity biosensor based on genetically modified Escherichia coli (E. coli) with green fluorescent protein (GFP) was developed for the evaluation of the toxicity of several hazardous heavy metal ions. The toxic metals include Cu(II), Cd(II), Pb(II), Zn(II), Cr(VI), Co(II), Ni(II), Ag(I) and Fe(III). The optimum fluorescence excitation and emission wavelengths of the optical biosensor were 400 ± 2 nm and 485 ± 2 nm, respectively. Based on the toxicity observed under optimal conditions, the detection limits of Cu(II), Cd(II), Pb(II), Zn(II), Cr(VI), Co(II), Ni(II), Ag(I) and Fe(III) that can be detected using the toxicity biosensor were at 0.04, 0.32, 0.46, 2.80, 100, 250, 400, 720 and 2600 μg/L, respectively. The repeatability and reproducibility of the proposed biosensor were 3.5%–4.8% RSD (relative standard deviation) and 3.6%–5.1% RSD (n = 8), respectively. The biosensor response was stable for at least five weeks, and demonstrated higher sensitivity towards metal toxicity evaluation when compared to a conventional Microtox assay.